FSH-Receptor Isoforms and FSH-dependent Gene Transcription in Human Monocytes and Osteoclasts - Robinson, Lisa J (2010)
Cells of the monocyte series respond to follicle stimulating hormone (FSH) by poorly characterized mechanisms. We studied FSH-receptors (FSH-R) and FSH response in nontransformed human monocytes and in osteoclasts differentiated from these cells. Western blot and PCR confirmed FSH-R expression on monocytes or osteoclasts, although at low levels relative to ovarian controls. Monocyte and osteoclast FSH-Rs differed from FSH-R from ovarian cells, reflecting variable splicing in exons 8–10. Monocytes produced no cAMP, the major signal in ovarian cells, in response to FSH. However, monocytes or osteoclasts transcribed TNFα in response to the FSH. No relation of expression of osteoclast FSH-R to the sex of cell donors or to exposure to sex hormones was apparent. Controls for FSH purity and endotoxin contamination were negative. Unamplified cRNA screening in adherent CD14 cells after 2 hours in 25 ng/ml FSH showed increased transcription of RANKL signalling proteins. Transcription of key proteins that stimulate bone turnover, TNFα and TSG-6, increased 2–3 fold after FSH treatment. Smaller but significant changes occurred in transcripts of selected signalling, adhesion, and cytoskeletal proteins. We conclude that monocyte and osteoclast FSH response diverges from that of ovarian cells, reflecting, at least in part, varying FSH-R isoforms.